2017
DOI: 10.1007/s12603-016-0725-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intestinal motility, mucosal barrier function, and inflammation in aged monkeys

Abstract: Objective: We aimed to examine the general health and intestinal physiology of young and old non-human primates with comparable life histories and dietary environments. Design: Vervet monkeys (Chlorcebus aethiops sabaeus) in stable and comparable social and nutritional environments were selected for evaluation. Health phenotype, circulating cytokines and biomarkers of microbial translocation (MT) were measured (n=26–44). Subsets of monkeys additionally had their intestinal motility, intestinal permeability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 50 publications
5
72
1
Order By: Relevance
“…The older baboons displayed a significant decrease in ZO-1, occludin, and JAM-A proteins, and an increase in claudin-2 expression, all of which correlated with increased permeability in the old aged group [66]. Another study in monkeys found that old monkeys have an increase in FITC dextran flux compared to young monkeys [67]. …”
Section: Barrier Pathophysiology In Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The older baboons displayed a significant decrease in ZO-1, occludin, and JAM-A proteins, and an increase in claudin-2 expression, all of which correlated with increased permeability in the old aged group [66]. Another study in monkeys found that old monkeys have an increase in FITC dextran flux compared to young monkeys [67]. …”
Section: Barrier Pathophysiology In Developmentmentioning
confidence: 99%
“…Several studies have reported a dysregulation in the intestinal immune homeostasis in different models of aging. Specifically, it has been shown that the function of the gut-associated immune system is impaired in elderly humans [67, 69, 73, 74]. …”
Section: Barrier Pathophysiology In Developmentmentioning
confidence: 99%
See 3 more Smart Citations